Dry Sliding Wear Behavior of B4C and Graphite Particulates Reinforced A356 Alloy Composites - R Jadhav, Pankaj; R Sridhar, B; Nagaral, Madeva; I Harti, Jayasheel; Auradi, V (International Journal of Engineering and Technology, 2018)
The present works manages readiness of the composites by mix stirring method. A356 amalgam 4 wt. % of B4C and A356-4 wt. % of Graphite and A356-4% B4C-4% Graphite hybrid composites were readied. To enhance the wetting and uniform conveyance of the particles, fortifications were preheated to a temperature of 500 Degree Celsius. The arranged MMCs are subjected to examining SEM instrument which affirms the homogenous uniform appropriation of smaller scale B4C and Graphite particles in the lattice combination without agglomeration. The wear protection of arranged composites was examined by performing dry sliding wear test utilizing DUCOM made stick on plate mechanical assembly. The tests were directed at a consistent heap of 3kg and sliding separation of 4000m over a speed of 100, 200 and 300 rpm. So also the other arrangement of investigations were led at consistent sped of 300 rpm and sliding separation of 4000m and with changing heap of 1kg, 2kg, and 3kg. The outcomes demonstrated that the wear protections of the composites were improved than the lattice material.Â Â